Keesaan Allah dalam Pemahaman Ilmu Tasawuf - Damanhuri Basyir (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
This papers describes a very general view on Tauhid in the Islamic  mystical thought. The ulama from the Sufis group, like other group of ulama,  intends to purify the Oneness concept of Allah. That is how such course becomes  a very serious theme in their discussion. Some of the thoughts somehow  contradict with their own expression and explanation, however they go to the  same conclusion about Allah in relation with the unity of existence. Their  discussion is around the truth of creator and the creation. This papers aims to  discuss the Sufis thought in order the complexity could become clearer and the  thought can be easily understood.